UPAYA OPTIMALISASI PRODUKSI ASI MELALUI PENYULUHAN POLA MAKAN IBU MENYUSUI - Cut Oktaviyana; Syarifah Masthura; Dewi Sartika; Fauziah Fauziah (JURNAL PENGABDIAN KEPADA MASYARAKAT BIDANG KESEHATAN, 2025)
The inability to produce an adequate supply of breast milk is frequently the primary factor leading to the premature cessation of exclusive breastfeeding. A lack of maternal understanding regarding healthy dietary patterns and the consumption of galactagogues (lactation-enhancing foods) poses a significant risk. Health education serves as a cognitive approach to improve maternal knowledge of nutrition during the lactation period. This study aims to enhance the knowledge of breastfeeding mothers concerning dietary habits as an effort to optimize breast milk production. This research employed a quantitative method with a pre-experimental "one-group pre-posttest design," conducted at the Krueng Barona Jaya Public Health Center (Puskesmas). The population consisted of 15 breastfeeding mothers, selected using a total sampling technique. Data were analyzed using univariate and bivariate analysis. The findings revealed that prior to the intervention, most respondents (67%) possessed a low level of knowledge. Following the health education session, the maternal knowledge level increased significantly, with 100% of participants falling into the high category. A T-test was performed to compare knowledge levels before and after the intervention, yielding a significant value of. This indicates a statistically significant difference in knowledge levels following health education. Health education should be consistently implemented by healthcare providers to enhance the knowledge of breastfeeding mothers, thereby supporting the practice of breastfeeding until the child reaches two years of age.